The rights-based approach to development : access to health care services at Ratshaatsha Community Health Centre in Blouberg Municipality of Limpopo - Rammutla, Chuene William Thabisa (University of Limpopo, 2012)
Section 27 of the Constitution of the Republic of South Africa, 1996 provides that everyone has a right to have access to health care. South Africa embraces the concept of universal health care coverage. Access to health care has four dimensions: geographic accessibility, availability, financial accessibility and acceptability. If there were barriers to access to health care, the stake-holders would be duty-bound to design interventions requisite to address those barriers. The aim of the study was to establish whether health care users enjoy the right to have access to health services at Ratshaatsha Community Health Centre (RCHC). The study used a combination of quantitative and qualitative research designs. While a questionnaire was used to collect quantitative data, focused group discussions and participant observations were employed to collect qualitative data. The following are the main findings of the study. Human rights instruments clearly spell out the indivisible and mutually supportive rights that persons have. There are barriers that often affect the rights to have access to health services at RCHC. For instance, the RCHC is not within a 25 km radius of some of the consumers of health care. The roads that link up the health care users and RCHC are in poor condition. The community is generally poverty-stricken. Many cannot afford, among others, the costs of basic needs, transport fares and opportunity costs. Travelling distance and time, scarce skills and lack of medication and equipment rank among demand-side and supply-side barriers to access to health care. Health care users often choose to consult churches and traditional healers. It is recommended that government should, among others, co-ordinate primary health care services in collaboration with churches and traditional healers; commission research into traditional health medicine and healing procedures and protocols of other health care providers; develop policy on cross-referral of patients; improve community participation; set minimum norms and standards for the delivery of alternative health care services; establish health care management guidelines for churches and traditional healers; integrate health care provisioning into IDPs; and provide health care in an integrated intergovernmental manner.
Thesis (M. Dev.) --University of Limpopo, 2013
Keywords: Health care services; Community health centre; Right to health -- South Africa; Health services accessibility -- Law and legislation; Community health services -- Law and legislation